Analisis Efisiensi Saluran Pemasaran Beras - Arifuddin, Saenal; Untari, Untari; Ineke, Ineke; Widyantari, Nursih (MuJAgri: Musamus Journal of Agribusiness, 2020)
This research is aimed to analyze the way of rice’s distribution and efficiency. This research use survey method and the place in Marga Mulya Village, Merauke district start from November until December 2012. This research take the datas that anlyze by margin distribution pattern, farmers share, vantage ratio of fund.The result is knowing there are 9 distribution ways that used by farmers in Marga Mulya. Distribution way I is distribution that more efficient than the other. Keywords: ways, distribution selling, efficiency